Penerapan Metode Rapid Application Development (RAD) dalam Pengembangan Aplikasi Penerimaan Peserta Didik Baru Berbasis Website - Febiani, Amelia; Supriadi, Fidi; Junaedi, Dani Indra (Yayasan Pendidikan Tanggui Baimbaian, 2024)
The role of information systems in improving the efficiency and quality of the education process has become a major concern for educational institutions. The process of admitting new students is one of the challenges often faced by various educational institutions, including SMP NU Darul Falah Subang. The problem faced is that the current process of registering and admitting new students still causes difficulties in managing and analyzing data efficiently and increasing the risk of errors. One solution to overcome these problems is the development of the Penerimaan Peserta Didik Baru application. The benefit of this application is to increase the efficiency of filling out forms, especially for students who register remotely, and simplify the archiving of new student data. The method used in making this application is Rapid Application Development. The Rapid Application Development method was chosen because of its focus on rapid development and adaptive to change, and involves active participation of users and developers throughout the process. This research aims to develop a web-based Penerimaan Peserta Didik Baru application using the Rapid Application Development method.